Optimization of fertilizer cow waste-based bokashi composting process using 3 types effective microorganism in smart pot sak - Mohd Ghazali, Mohd Sabri; Garfansa, Marchel Putra; Iswahyudi, Iswahyudi; Sholeh, Mohammad Shoimus (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2024)
Bokashi fertilizer is the result of recycling organic waste through a composting process that functions to improve soil health and plant production. However, the quality of organic waste and the composting process time are affected by the type of Effective Microorganisms used. This study was designed to evaluate the process and quality of organic waste produced from three types of Effective Microorganisms (EM4, Eco Farming, and MA11). Organic waste consisting of cow dung, rice husk, and bran mixed with each type of microorganism solution according to the treatment of 10, 15, and 20 ml/10 kg weight of organic waste with a composting time of 30 days. pH, Temperature, Color, Air content, N-organic, C-organic, C/N Ratio, Potassium, and Phosphate were recorded in this study. The results showed that 20 mL MA11 provided a faster composting process with an optimal Ph level and C/N ratio. In addition, the water content produced was lower and there was an increase in nutrients compared to other treatments. The use of MA11 in optimum quantities will produce good quality organic waste and quickly without causing environmental problems in its application to soil.